Evaluation of fracture resistance and fracture pattern of roots following canal preparation by hand and rotary instrumentation (Mustansiria Dental Journal, 2018)
The present in-vitro study was undertaken to compare fracture strength of rootsfollowing canal preparation by hand (step-back) and rotary (ProTaper)instrumentation and, further, to determine the direction of fracture lines.Twenty freshly extracted human mandibular premolars were randomly dividedinto two groups of 10 teeth each. In Group I, canals were prepared with step-backtechnique using standardized nickel-titanium K-files. In Groups II, canals wereprepared with crown-down technique using ProTaper rotary files. Afterinstrumentation, a vertical load was applied by means of a spreader attached to theInstron testing machine and inserted into the canal until fracture occurred. The rootswere subsequently examined under a stereomicroscope with 10X magnification todetermine the direction of fracture lines. The results were statistically analyzed usingpaired t-test.The Mean fracture load was 10.420 ± 3.451 kg for K-files and 12.40 ± 4.064 forProTaper files, the differences between the two groups were not statisticallysignificant (p>0.05). Most of the fracture lines observed were in bucco-lingualdirection, followed by proximal and compound fractures.Increased canal taper by ProTaper instrumentation technique did not increase thefracture susceptibility of mandibular premolars any more than conventional step-backK-file preparations and may even increase the fracture resistance.